Product Line Design with Seller-Induced Learning - Xiong, Hui; Chen, Ying-Ju (Management Science, 2014)
In practice, some well-established service providers (sellers) offer one-time experiences or product demonstrations for the services that have been introduced to the market for years. Such activities, labeled as seller-induced learning, not only help the consumers learn more about themselves but also exploit the consumers by elaborating on the consumer heterogeneity. When the seller-induced learning completely resolves the consumers' valuation uncertainty, it can facilitate a more sophisticated price discrimination scheme and may give rise to a relatively more efficient allocation. Nevertheless, if there is residual valuation uncertainty, the seller may abandon the seller-induced learning to avoid the exacerbated ex post cannibalization. We show that an exploding offer shall sometimes be offered in conjunction with the seller-induced learning to encourage immediate purchases when uncertainty arises in only some consumers. We identify regimes under which the seller-induced learning is charged at a strictly positive price. Under these regimes, the seller need not sacrifice the ex post efficiency upon inducing consumer learning. Therefore, our result indicates that the seller-induced learning may eliminate the conflict between rent extraction and efficiency initiatives. However, quality distortion prevails when the seller provides an identical menu for all the consumers or the free seller-induced learning. This paper was accepted by J. Miguel Villas-Boas, marketing.